Measuring of quality of life in Polish metropolises – application of method of standardized indicators - Walaszek, Marzena (Rozwój Regionalny i Polityka Regionalna, 2013)
Quality of life surveys should be an important part of the comprehensive management of urban areas. This especially refers to Poland where the integration but also a competition between metropolises has just started. Positioning studies conducted in relation to the local communities living in large cities are a valuable source of information. They are a useful tool to identify the attractiveness of metropolises which helps to compare their position to other cities, diagnose potential weaknesses and the application of development strategies allowing to increase the quality of life and hence the competitiveness. The purpose of the paper is analysis of quality of life indicators in Polish metropolises and measuring their position in term of quality of life, using the selected indicators. The study was conducted on the example of 10 largest cities in Poland: Warszawa, Poznań, Wrocław, Katowice, Lublin, Bydgoszcz, Gdańsk, Kraków, Szczecin, Łódź. The selection criterion was the number of urban residents which ranges from 307 thousands (Katowice) to 1,7 million (Warszawa). It was decided that the analysis will focus on indicators that illustrate different dimensions of quality of life. The data were classified into 8 categories that reflect different aspects of quality of life in cities